Analisis Penataan Ruang Parkir Pasar Keputran Kota Surabaya - Aditia Eka Wicaksono (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Keputran Market is one of the main markets located in the middle of the city with a market area of ​​2550 m2, making Keputran Market have complex problems, especially parking areas. Keputran Market Surabaya is located in a densely trafficked location and Keputran Market Surabaya is located between 2 intersections, between Jalan Sulawesi, Jalan Dinoyo, and Jalan Pandegiling. The parking area available at Keputran Market Surabaya is 408 m2. This capacity is no longer adequate, so visitors cannot park in their proper places. Many motorbikes and cars choose to park on street. The large number of vehicles parked on street causes the available road capacity to narrow, often causing congestion. Based on the results of the analysis that has been carried out, the following results were obtained, Parking volume on peak days reached 343 vehicles with details of 281 for motorbikes and 62 for cars. While only 160 SRP are available, this means that the existing parking space is no longer able to be a parking lot to accommodate the number of vehicles. The average parking duration of motorcycles is 196 minutes per day, and the average parking duration of cars is 218 minutes per day. The turnover rate of motorcycles in one day reaches 2.10 times, then for cars in one day it reaches 2.38 times. Meanwhile, the forecast for vehicle parking growth that will occur in the next 5 years is increasing every year, where for motorcycles it is 10.64%, and cars are 7.13%. The 2021 SRP for motorcycles is 147 SRP and cars are 36 SRP. The 2022 SRP for motorcycles is 177 SRP and cars are 40 SRP. The 2023 SRP for motorcycles is 210 SRP and cars are 45 SRP. The 2024 SRP for motorcycles is 247 SRP and cars are 50 SRP. The 2025 SRP for motorcycles is 28 SRP and cars are 56 SRP. SRP in 2026 for motorcycles is 332 SRP and cars is 61 SRP.